Interactive Environmental Garden and Its Role in Rural Tourism Development, Slovakia - Bihunova, Maria (Turizam, 2018)
Rural tourism is still not effectively developed in Slovakia. There are documents and activities of nongovernmental organisations that promote the countryside, culture, agricultural activities, the uniqueness of the landscape but they are not systemic and without strong legal background. In the southern part of Slovakia – The Danube Lowland - is rich with natural, cultural and architectural sites, thermal springs, possibilities for water tourism in the river Small Danube, and places for agro tourism, etc. The development of the region supports the character of the terrain and appropriate conditions for modest cycling. The Environmental Education Centre (EEC) Dropie – an educational organization of the Slovak Environmental Agency in Zemianska Olča is a unique site providing recreational and educational activities, with the possibility to spend overnights in the centre. It is the biggest environmental centre in Slovakia and it is aimed (except the issues regarding natural protection) at the education and promotion of the bustard (Otis tarda) one of the heaviest flying birds in the world. This bird has a territory of the natural occurrence along the border between Slovakia, Hungary and Austria. The EEC Dropie is situated in the agricultural land, characterized by large-scale block fields, surrounded by Special Protection Area of the Island Meadows and the NATURA 2000 site. The students of the Slovak University of Agriculture in Nitra, Faculty of Horticulture and Landscape Engineering were invited to create landscape architectural designs for the centre focusing on easier and demonstrative outdoor education for the public and especially children.